Implementasi Peraturan Walikota Mataram Nomor 20 Tahun 2018 Terhadap Kepatuhan Zakat Profesi Dan Kesadaran Pajak Aparatur Sipil Negara - L. Dendy Rahman Prayatna; Fahrurrozi Fahrurrozi; Zulpawati Zulpawati (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study analyses the implementation of Mataram Mayor Regulation Number 20 of 2018 in managing ASN professional zakat, particularly its effect on zakat receipts, institutional synergy, and awareness in fulfilling zakat and tax obligations. It uses a qualitative approach with an empirical juridical method. Data were obtained through interviews with ASN, Zakat Collection Unit administrators, BAZNAS Mataram City managers, and counsellors from KPP Pratama West Mataram, alongside regulatory documents and zakat receipt reports. Data were analysed through reduction, presentation, and conclusion drawing, while validity was tested through source triangulation, member checking, and peer discussion. The findings show that the regulation increases and stabilises ASN receipts through a direct deduction system. ASN ZIS receipts rose from around Rp2.5 billion in 2016 to around Rp6.6 billion by October 2025. However, ASN compliance remains administrative because it is driven by payroll, not substantive awareness. This study emphasises regulatory harmonisation, zakat-tax literacy, and reporting transparency.